Optimizing the circulation in the prone patient. Issue 3 (June 2016) - Jozwiak, Mathieu; Monnet, Xavier; Teboul, Jean-Louis
Abstract : Purpose of review: Prone positioning is recommended as a rescue therapy to improve arterial oxygenation in patients with severe acute respiratory distress syndrome (ARDS). In this review, we summarize the macro and the microcirculatory effects of prone positioning and emphasize which hemodynamic variables can be monitored when this therapy is applied. Recent findings: Early and prolonged prone positioning sessions significantly decrease the mortality of patients with severe ARDS. Prone positioning increases cardiac preload and decreases right ventricular afterload in patients with ARDS under protective ventilation and maximal lung recruitment. This results in an increase in cardiac output only in patients with preload reserve, emphasizing the important role of preload in the hemodynamic effects of prone positioning. Prone positioning might also exert some effects on regional and/or local blood flows, which mainly result from the increase in intra-abdominal pressure. Because prone positioning does not produce a significant increase in intra-abdominal pressure, it does not exert deleterious effects on the microcirculation of intra-abdominal organs. Summary: Prone positioning generally exerts beneficial macrocirculatory effects, which can result in increased cardiac output in patients with preload reserve without negatively altering regional circulations.